2020
DOI: 10.1007/s10869-020-09696-2
|View full text |Cite
|
Sign up to set email alerts
|

Should We Agree to Disagree? The Multilevel Moderated Relationship Between Safety Climate Strength And Individual Safety Motivation

Abstract: M. (2020). Should we agree to disagree? The multilevel moderated relationship between safety climate strength and individual safety motivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…Similarly, González-Romá et al (2002) found support for a climate level and strength interaction in three of six (50%) regression tests involving climates for support, goal orientation, and innovation and the outcomes of group satisfaction and commitment. More recently, Flatau-Harrison et al (2021) proposed that safety climate strength moderates the individual safety climate level–safety motivation relationship. Initial analyses did not support this interaction; however, after reoperationalizing workgroups into larger units, they found a significant interaction.…”
Section: The Interaction Between Climate Level and Strengthmentioning
confidence: 99%
“…Similarly, González-Romá et al (2002) found support for a climate level and strength interaction in three of six (50%) regression tests involving climates for support, goal orientation, and innovation and the outcomes of group satisfaction and commitment. More recently, Flatau-Harrison et al (2021) proposed that safety climate strength moderates the individual safety climate level–safety motivation relationship. Initial analyses did not support this interaction; however, after reoperationalizing workgroups into larger units, they found a significant interaction.…”
Section: The Interaction Between Climate Level and Strengthmentioning
confidence: 99%
“…This highly noble behavior is, however, concerning considering the many productivity and health-related complaints that originate from presenteeism, especially so in the current global context of a virulent pandemic. Even positive job characteristics enacted through safety culture and climate can have large and variable implications on health care employee motivation to carry out their jobs safely (Flatau-Harrison et al, 2020), which is concerning given that research already shows that presentees are more likely to make safety errors and mistakes compared with nonpresentees (Niven & Ciborowska, 2015). Employers should be wary of this and be vigilant to maintaining strict sick leave policies in the workplace, which remove the decision-making capability of individuals when unwell.…”
Section: Practice Implicationsmentioning
confidence: 99%
“…When one internalizes the value, a behaviour is enacted because it is of personal importance, thus no external monitoring is required (Tyler & Blader, 2005). Recent studies have shown that safety motivation – the degree to which one values and places personal importance on safe work practices – is a powerful determinant of safety behaviour (Flatau‐Harrison, Griffin, & Gagne, 2020; Sawhney & Ciglarov, 2019). Nevertheless, meta‐analytic evidence presented by Clarke (2013) suggests that, although placing high personal importance on safe work predicts the more volitional forms of safety behaviour, it seems to be less important in driving safety compliance, and longitudinal research by Neal and Griffin (2006) did not detect a relationship between safety motivation and safety compliance.…”
Section: Introductionmentioning
confidence: 99%